"Dark" Heritage? Nudging the Discussion. (4th May 2022) - Thomas, Suzie
ABSTRACT: A particular strand within cultural heritage studies has been developing, known as "dark" heritage. However, its usage does not always point to a clear or universal definition, but rather tacit assumptions over what it might mean. The author and colleagues have contributed to perpetuating the continued "dark heritage" referencing through the ongoing research collective "Lapland's Dark Heritage". Investigating the ongoing impacts of the legacy of the Second World War in Finnish Lapland, the project has shed light on local sentiments towards both tangible and intangible reminders of conflict. It has critiqued the apparent state-sanctioned silencing of some aspects of that past, and analysed the ruptures caused to traditional Northern lifeways in the continued context of colonial frameworks. Yet scholars are not merely innocent observers. This paper approaches "dark" heritage on three levels. Firstly, it summarizes Lapland's Dark Heritage and its impact on discussions and actions outside academia, including heritage management policy. Secondly, it problematizes the term and its development through the frameworks of critical heritage – challenging the assumptions inherent in the term concerning what makes its focus either "dark" or "heritage". Finally, it takes a wider view, questioning whether the analyses that scholars make have relevance or interest to the wider society. By so doing, the paper contributes to the broader debate concerning the future directions of heritage studies, including the apparent disconnect between applied heritage management training and methods, and more theoretical critical heritage discourses.